Privilegios territoriales en la España borbónica del siglo xviii - Sergio Solbes Ferri (Mélanges de la Casa de Velázquez, 2016)
The article seeks to answer the question whether or not there was deliberate intent to modify the ancestral traditions of territories in Spain where fiscal privileges persisted after the War of Succession. It enquires whether there was an intention to bring these territories into a uniform tax regime. The conclusion is that there certainly was such an intent and it was in fact pursued, but that nonetheless some particular nuances were allowed to survive in the territories concerned and compromises were negotiated with local elites and institutions.